Targeted Interventions to Increase Blood Pressure and Decrease Anaesthetic Concentrations Reduce Intraoperative Burst Suppression: A Randomised, Interventional Clinical Trial - Georgii, Marie-Therese; Kreuzer, Matthias; Fleischmann, Antonia; Schuessler, Jule; Schneider, Gerhard; Pilge, Stefanie (Frontiers in Systems Neuroscience, 2022)
Background It has been suggested that intraoperative electroencephalographic (EEG) burst suppression (BSupp) may be associated with postoperative neurocognitive disorders in the elderly, and EEG-guided anaesthesia may help to reduce BSupp. Despite of this suggestion, a standard treatment does not exist, as we have yet to fully understand the phenomenon and its underlying pathomechanism. This study was designed to address two underlying phenomena – cerebral hypoperfusion and individual anaesthetic overdose. Objectives We aimed to demonstrate that targeted anaesthetic interventions – treating intraoperative hypotension and/or reducing the anaesthetic concentration – reduce BSupp. Methods We randomly assigned patients to receive EEG-based interventions during anaesthesia or EEG-blinded standard anaesthesia. If BSupp was detected, defined as burst suppression ratio (BSR) >0, the primary intervention aimed to adjust the mean arterial blood pressure to patient baseline (MAP intervention) followed by reduction of anaesthetic concentration (MAC intervention). Results EEG-based intervention significantly reduced total cumulative BSR, BSR duration, and maximum BSR. MAP intervention caused a significant MAP increase at the end of a BSR>0 episode compared to the control group. Coincidentally, the maximum BSR decreased significantly; in 55% of all MAP interventions, the BSR decreased to 0% without any further action. In the remaining events, additional MAC intervention was required. Conclusions Our results show that targeted interventions (MAC/MAP) reduce total cumulative amount, duration, and maximum BSR>0 in the elderly undergoing general anaesthesia. Haemodynamic intervention already interrupted or reduced BSupp, emphasising the role of hypotension-induced cerebral hypoperfusion as an important pathomechanism of intraoperative BSupp.